Avaliação das patologias em sistema predial hidrossanitário: um estudo de caso - Nascimento, Thiago Monteiro do (Brasil, 2024)
This thesis aims to evaluate the pathologies of a plumbing system in a building located in Manaus, AM. This work aims to evaluate the pathology of a plumbing system in a building located in Manaus/AM. The research was carried out through a qualitative and quantitative approach, using direct observation, application of checklists and BIM modeling to identify and map the pathologies present. The results revealed the occurrence of leaks, pressure problems and inadequacies in devices, with an impact on the daily lives of residents and employees of the building. The proposed solutions range from simple device replacements to the need for more complex interventions by an engineer. The results show that adequate maintenance and compliance with technical standards are crucial for the functionality and safety of buildings, and that BIM modeling is an effective tool for identifying and solving pathologies in plumbing systems.